Factors Associated with Free Flap Failures in Head and Neck Reconstruction. (6th August 2019) - Crawley, Meghan B.; Sweeny, Larissa; Ravipati, Prasanti; Heffelfinger, Ryan; Krein, Howard; Luginbuhl, Adam; Goldman, Richard; Curry, Joseph
Abstract : Objective: To investigate causes of failure of free flap reconstructions in patients undergoing reconstruction of head and neck defects. Study Design: Case series with chart review. Setting: Single tertiary care center. Subjects and Methods: Patients underwent reconstruction between January 2007 and June 2017 (n = 892). Variables included were clinical characteristics, social history, defect site, donor tissue, ischemia time, and postoperative complications. Statistical methods used include univariable and multivariable analysis of failure. Results: The overall failure rate was 4.8% (n = 43). Intraoperative ischemia time was associated with free flap failures (odds ratio [OR], 1.062; 95% confidence interval [CI], 1.019‐1.107; P =. 004) for each addition of 5 minutes. Free flaps that required pedicle revision at time of initial surgery were 9 times more likely to fail (OR, 9.953; 95% CI, 3.242‐27.732; P <. 001). Patients who experienced alcohol withdrawal after free flap placement were 3.7 times more likely to experience flap failure (OR, 3.690; 95% CI, 1.141‐10.330; P =. 031). Ischemia time remained an independent significant risk factor for failure in nonosteocutaneous free flaps (OR, 1.105; 95% CI, 1.031‐1.185). Alcohol withdrawal was associated with free flap failure in osteocutaneous reconstructions (OR, 5.046; 95% CI 1.103‐19.805) while hypertension was found to be protective (OR, 0.056; 95% CI, 0.000‐0.445). Conclusion: Prolonged ischemia time, pedicle revision, and alcohol withdrawal were associated with higher rates of flap failure. Employing strategies to minimize ischemic time may have potential to decrease failure rates. Flaps that require pedicle revision and patients with a history of significant alcohol use require closer monitoring.